Governance and Management of Protected Health Information in Health Records, Health Informatics, and Hospital Administrative Systems - Alotaibi, Hamed Abdullah; Alahazmi, Khamis Nazal; Alsaad, Yahya Mohammed H; Alsharif, Faisal Ahmed; Hagawe, Sultan Mohammed; Al Sinan, Saleh Hamad Dahin; Hamedhi, Hassan Abdullah Hadi; Kulaibi, Ali Muhammad Yahya; Faqihi, Abdullah Hussein Mohsen; Asseri, Khaled Yahya Ahmed; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Protected Health Information (PHI) is a fundamental component of modern healthcare systems, particularly within digital health records, health informatics platforms, and hospital administrative systems. Regulatory frameworks such as the Health Insurance Portability and Accountability Act (HIPAA) define PHI and establish standards for its protection to preserve patient privacy, trust, and legal accountability. Aim: This article aims to examine the governance and management of PHI within health records, health informatics, and hospital administrative systems, highlighting ethical, legal, and clinical implications and clarifying the roles of healthcare professionals in safeguarding sensitive patient information. Methods: A descriptive and analytical approach was employed, reviewing regulatory frameworks, healthcare workflows, and professional practices related to PHI handling. The article integrates legal provisions, institutional roles, and clinical scenarios to analyze risks, safeguards, and governance strategies across healthcare settings. Results: The review demonstrates that effective PHI management depends on coordinated responsibilities among medical records specialists, medical secretaries, health informatics professionals, and hospital management. Technical safeguards such as encryption, role-based access, audit trails, and deidentification significantly reduce privacy risks while supporting clinical efficiency and research innovation Conclusion: Robust PHI governance enhances patient trust, clinical quality, and regulatory compliance. Integrating ethical judgment, continuous training, and secure information systems is essential as healthcare becomes increasingly data driven.